The Discursive Construction of Strategies for Implementing Anti-Corruption Education at State Islamic Higher Educational Institutions - A. Rahman, Mustafa (Jurnal Ilmiah Peuradeun, 2022)
Corruption is so pervasive in the Republic of Indonesia that it has becomea rampant conundrum in various economic, social, educational, and even religious sectors. Using discursive analysis as the research methodology with the Foucauldian paradigm, this paper aimed at identifying and describing the strategies used in the discursive construction of the implementation of anti-corruption education (Pendidikan Antikorupsi, PAK) by three State Islamic Higher Educational Institutions (Perguruan Tinggi Keagamaan Islam Negeri, PTKINs) in Aceh. Given fairness of the geographical location, Ar-Raniry State Islamic University, Lhokseumawe State Islamic Institute and Teungku Dirundeng State Islamic College were selected as the research sites. The data were collected by interviewing the leaders of three PTKINs—rectors, deans, and heads of departments—through questionnaires and focus group discussions with lecturers. The findings indicate that the three PTKINs generally have strategies for implementing PAK; separate subjects, incorporating the PAK curriculum into related subjects, such as fiqh (Islamic jurisprudence), and state resilience. PAK is also integrated into students' activities that take place on campus. Both internal and external factors, such as overloaded subjects in the departments and insufficient support from the community, hamper PAK at the PTKINs.